PENGARUH PROMOSI, BRAND AMBASSADOR, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK BODY LOTION SCARLETT WHITENING (STUDI KASUS MASYARAKAT DI KOTA DEPOK) - Agustini; Nurchaeliza (Jurnal Gici Jurnal Keuangan dan Bisnis, 2024)
The purpose of this study is to be able to determine and to analyze the effect of promotion, brand ambassador and product quality on purchasing decisions for Scarlett Whitening Body lotion products for people in Depok City. The type of research method used is quantitative method with data collection methods using a questionnaire.. For the number of samples of this study were 100 respondents. In the regression test results show the results with a figure of 77.8% explaining that the purchasing decision factor by price, product quality, and brand while the remaining 22.2% is explained by other factors not examined in this study. Meanwhile, the results of the F test of all variables show that simultaneously the influence between the variables of purchasing decisions, promotion, brand ambassadors and product quality simultaneously has a significant effect on purchasing decisions with the results of the analysis, namely the Fcount value of 116.657 is greater than Ftable = 2.700. For the T test results, it shows that the promotion variable shows the tcount (18.483) where the ttable (1.985) says that the promotion variable has a significant effect on purchasing decisions for Body lotion products in the community in Depok City. Meanwhile, for the brand ambassador variable with the results of tcount (1.438) where ttable (1.985) and for the product quality variable with the results of tcount (0.585) where ttable (1.985) shows the results that the brand ambassador and product quality variables do not have a significant effect on purchasing decisions for Body lotion products in the community in Depok City. The dominant variable in this study and influencing purchasing decisions for Body lotion in the community in Depok City is the promotion variable.